Plant diversity in secondary, montane grasslands – a case study of the abandoned plantations of Mariepskop Mountain, South Africa - Swemmer, Anthony M.; Lerm, Rion E.; Thompson, Dave I.; Graf, Jan A.; Stone, Lynne; Mashele, Mightyman (Frontiers in Conservation Science, 2024)
Grasslands are one of the most threatened terrestrial ecosystem types, and montane grasslands of particular conservation concern. Despite high rates of transformation in recent decades, croplands and plantations are being abandoned in parts of many countries, creating an opportunity for conservation of montane grasslands through restoration. We report on the changes in the cover of major vegetation types (indigenous forest, grassland, and plantations) between 1935 and 2022, in an area that was intensively afforested from 1930 to 1960 and abandoned in 2000. Montane grassland at the site declined from over 50% of all landcover to below 15%, but subsequently recovered to 30% within 20 years. Many former plantations developed into secondary grassland with estimated gamma plant species richness of 231 for herbaceous species and 45 for savanna species. These are high values considering the size of the study area (4000 ha), and comparable to estimates from primary grassland sites in the broader region. However, at the scale of 1 m2 sampling quadrats, richness in the secondary grasslands was below that recorded in the last remaining patches of primary grassland at the site (means of 2.6 versus 4.7 for graminoid species, and 1.9 versus 2.9 for forbs). Some of the former Eucalyptus plantations had transformed into novel savannas dominated by fire-tolerant, resprouting trees, and may require more active restoration. Secondary grasslands such as those reported on here could potentially make a significant contribution to the conservation of montane biodiversity over the coming decades, warranting further research (both socio-economic and ecological) on the factors that lead to abandonment and promote the emerge of secondary grasslands of high diversity.